STUDY OF ANTIBODIES TO OPPORTUNISTIC ENTEROBACTERIA IN THE BLOOD OF ADULTS - Tursunboy qizi, Fozilova Sarvinoz; Alisher qizi, Ozodbekova Sitara; Abdukayumovich, Adilov Abdujabbor; Rustamovna, Bekchanova Mahfuza (Journal of Medical Genetics and Clinical Biology, 2024)
Background: Opportunistic enterobacteria (OE), including various Gram-negative bacteria, are known to cause infections, particularly in immunocompromised individuals. Specific Background: Despite their clinical relevance, there is limited data on the prevalence of antibodies against these bacteria in the general adult population. Knowledge Gap: The extent to which antibodies to opportunistic enterobacteria are present in serum samples from healthy adults has not been thoroughly investigated. Aims: This study aimed to evaluate the presence and frequency of antibodies to seven types of Gram-negative opportunistic enterobacteria in adult serum samples using enzyme-linked immunosorbent assay (ELISA). Results: The analysis revealed a significant prevalence of antibodies against the bacteria E. coli, Proteus vulgaris, Citrobacter freundii, Klebsiella pneumoniae, Enterobacter aerogenes, Enterobacter cloacae, and Pseudomonas aeruginosa among the subjects. Novelty: This research provides new insights into the widespread presence of antibodies to OE in a healthy adult population, highlighting previously underexplored immunological responses. Implications: These findings could enhance diagnostic approaches and inform treatment strategies for infections caused by opportunistic enterobacteria, potentially leading to improved management of such infections in clinical settings.